Performance of a Simplified Wall Motion Score Index Method for Noncardiologists to Assess Left Ventricular Ejection Fraction. (22nd November 2011) - Lebeau, Réal; Potter, Brian J.; Sas, Georgetta; Moustafa, Sherif; Di Lorenzo, Maria; Soulieres, Vicky; Beaulieu, Yannick; Sauvé, Claude; Amyot, Robert; Serri, Karim
Abstract : Backgrounds . For emergency physicians performing a goal-directed transthoracic echocardiogram (TTE), a reliable estimate of LVEF must be obtained rapidly. We compared rapid LVEF estimates obtained from short axis sections to those obtained from apical sections using two methods of evaluation. Methods . The TTE's of 6 patients were interpreted by 16 echo-proficient readers (PRO group) and 105 novice readers (NOV group). LVEF was assessed by each group. The strategies consisted of either a global visual estimation (VIS) of LVEF or semiquantitative (SQ) methods. Results . Using RNV and BIP as a reference standard, NOV readers performed better with the SQ method than global visual estimation. For NOV readers, best agreement was achieved with the 234C sequence in low LVEF situations, but with the BMA series in normal LVEF settings. Neither series of views was better than the other in the setting of mild LVEF depression. Conclusion . Semi-quantitative method was superior to global visual estimation of LVEF in NOV group in most of the LVEF ranges.